3D genome landscape of primary and metastatic colorectal carcinoma reveals the regulatory mechanism of tumorigenic and metastatic gene expression - Xiang Xu; Jingbo Gan; Zhaoya Gao; Ruifeng Li; Dandan Huang; Lin Lin; Yawen Luo; Qian Yang; Jingxuan Xu; Yaru Li; Qing Fang; Ting Peng; et al. (Communications Biology)
Abstract Colorectal carcinoma (CRC) is a deadly cancer with an aggressive nature, and how CRC tumor cells manage to translocate and proliferate in a new tissue environment remains not fully understood. Recently, higher-order chromatin structures and spatial genome organization are increasingly implicated in diseases including cancer, but in-depth studies of three-dimensional genome (3D genome) of metastatic cancer are currently lacking, preventing the understanding of the roles of genome organization during metastasis. Here we perform multi-omics profiling of matched normal colon, primary tumor, lymph node metastasis, liver metastasis and normal liver tissue from CRC patients using Hi-C, ATAC-seq and RNA-seq technologies. We find that widespread alteration of 3D chromatin structure is accompanied by dysregulation of genes including SPP1 during the tumorigenesis or metastasis of CRC. Remarkably, the hierarchy of topological associating domain (TAD) changes dynamically, which challenges the traditional view that the TAD structure between tumor and normal tissue is conservative. In addition, we define compartment stability score to measure large-scale alteration in metastatic tumors. To integrate multi-omics data and recognize candidate genes driving cancer metastasis, a pipeline is developed based on Hi-C, RNA-seq and ATAC-seq data. And three candidate genes ARL4C, FLNA, and RGCC are validated to be associated with CRC cell migration and invasion using in vitro knockout experiments. Overall, these data resources and results offer new insights into the involvement of 3D genome in cancer metastasis.